ScriptsMap: A Tool for Designing Multi-Method Policy-Making Workshops - Ackermann, Fran; Anderson, D.; Eden, C.; Richardson, G. (Baywood Publishing Company, 2011)
This paper reports on the development and structure of a framework – ScriptsMap – intended to facilitate the design of mixed method policy-making workshops. The ScriptsMap framework aims to provide a means of articulating and combining activities (which a script specifies) from two or more methods so that a facilitator or group facilitation team can construct, with the framework’s aid, a thoughtful and careful design for a workshop. To provide an example of the framework, the combination of system dynamics group model building and group problem structuring incorporating causal mapping with the use of a Group Support System is used. The paper will illustrate ScriptsMap’s structure through an example of the use of the framework in practice.